2006
DOI: 10.1007/s10633-006-9015-z
|View full text |Cite
|
Sign up to set email alerts
|

The photopic negative response of the flash electroretinogram in retinal vein occlusion

Abstract: The photopic negative response (PhNR) has recently been shown to be severely affected in central retinal artery occlusion (CRAO), despite relative preservation of the cone b-wave compared to that in the healthy unaffected fellow eye. The aim of this study was to test how the PhNR of the flash electroretinogram (ERG) is affected in human retinal vein occlusion. PhNR was elicited with red stimuli (1 cd s/m2, 5 cd s/m2, and 7 cd s/m2 with 4 ms duration) and blue background (10 cd/m2). Standard Ganzfeld flash ERG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…The PhNR has been reported to reflect the RGC function and serves as a good indicator of severity of the damage of this retinal layer in several types of retinal diseases [10,11,12,13,14,15]. Our results showed that: (1) the PhNR is reduced in patients with CRAO, (2) a b/a ratio <1.0 was more frequently observed when the photopic ERG recordings were elicited by long-duration stimuli, (3) the degree of the reduction was correlated with the severity of the ocular ischemia, i.e., the amplitude decreased as the severity increased, and (4) the PhNR of the LF photopic ERG was relatively well preserved in eyes which attained a relatively good visual function following the CRAO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PhNR has been reported to reflect the RGC function and serves as a good indicator of severity of the damage of this retinal layer in several types of retinal diseases [10,11,12,13,14,15]. Our results showed that: (1) the PhNR is reduced in patients with CRAO, (2) a b/a ratio <1.0 was more frequently observed when the photopic ERG recordings were elicited by long-duration stimuli, (3) the degree of the reduction was correlated with the severity of the ocular ischemia, i.e., the amplitude decreased as the severity increased, and (4) the PhNR of the LF photopic ERG was relatively well preserved in eyes which attained a relatively good visual function following the CRAO.…”
Section: Discussionmentioning
confidence: 99%
“…The photopic negative response (PhNR) of the photopic ERG which originates from the neural activity of the RGCs has been used to assess the function of RGCs in experimental animals [9, 10] and in humans with retinal and optic nerve pathology [10,11,12,13,14,15]. The findings of these experiments prompted us to investigate the relationship of the PhNR of the photopic ERGs with the degree of circulatory disturbances in eyes with a CRAO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 A number of studies suggest that the PhNR in the photopic ERG originates primarily from activity of RGCs and their axons. [1][2][3][4][5][6][7][8][9] In clinical studies using full-field ERGs, the PhNR amplitude was reduced in various diseases that involves RGC damageFfor example, glaucoma, [3][4][5] retinal vascular disease, 6,7 and optic nerve diseases. [8][9][10] Several researchers measured PhNR by using focal macular ERG in humans and monkeys.…”
Section: Introductionmentioning
confidence: 99%
“…This late component, known as the photopic negative response (PhNR), was suggested to originate from the spiking activity of ganglion cells, with possible contributions from amacrine and glial cells [3]. Furthermore, the PhNR was also shown to be reduced in human diseases with a predominant dysfunction of the ganglion cells, as in glaucoma [4][5][6][7], optic neuropathy [8], optic nerve atrophy [9], diabetic retinopathy [10,11], and retinal artery and vein occlusions [12,13]; one study failed to demonstrate a PhNR reduction in advanced glaucoma [14]. The recording conditions used to elicit the PhNR were initially a monochromatic red stimulus on a blue rodsaturating background [3].…”
Section: Introductionmentioning
confidence: 99%